THE PRESIDENT'S PREROGATIVE IN GRANTING CLEMENCY TO NARCOTICS PRISONERS FROM THE PERSPECTIVE OF MAQASYIDUL SYARIAH - Muh. Djumarsyil; Ahmad Riyas Sauqy; Kurniati Kurniati (PT. Altin Riset Publishing, 2026)
The phenomenon of granting clemency to narcotics prisoners in Indonesia, as part of the president's prerogative, raises tensions between legal certainty and humanitarian considerations. This research aims to analyze the mechanism and legitimacy of granting clemency through the ethical perspective of Islamic law, especially maqāṣid al-syarī' ah. By using normative legal research procedures through legislative, conceptual, and problem analysis approaches, this research examines primary and secondary legal materials. The main findings say that maqāṣid al-Syarī'ah provides a comprehensive evaluation framework, in which clemency can be morally justified if it is oriented towards the protection of the soul (ḥifẓ al-nafs), the restoration of ideas (ḥẓ al-aql) via rehabilitation, and restorative justice. However, research concludes that this prerogative should not ignore the public interest (maslaḥah'āmmah) as the highest consideration. The implication is that the clemency policy requires extreme prudence to avoid weakening law enforcement and justify balancing the justice of people and the protection of citizens from the dangers of narcotics.